1998
DOI: 10.1094/cchem.1998.75.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Relating Rice Milling Quality Changes During Adsorption to Individual Kernel Moisture Content Distribution

Abstract: Cereal Chem. 75(1):129-136Several varieties of rough rice that were either stored for an extended period of time or freshly harvested were conditioned to initial moisture contents ranging from 10 to 17%. After the individual kernel moisture content distributions were measured, the samples were soaked in water at temperatures ranging from 10 to 40°C. The samples were then dried and milled. The bulk critical moisture content, at which head rice yield began to decline due to moisture adsorption, ranged from 12.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…3A), although significant differences were observed only with the Wells cultivar. Increased fissured-kernel percentages in response to HMCs below optimal levels agree with the findings of Siebenmorgen et al (1998Siebenmorgen et al ( , 2007. In contrast, the impact of HMC level on brown rice fissured-kernel percentages was significant for all cultivars (Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…3A), although significant differences were observed only with the Wells cultivar. Increased fissured-kernel percentages in response to HMCs below optimal levels agree with the findings of Siebenmorgen et al (1998Siebenmorgen et al ( , 2007. In contrast, the impact of HMC level on brown rice fissured-kernel percentages was significant for all cultivars (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Differences in fissured-kernel percentages were minimal between the 19 and 23% HMC levels, with statistical difference observed only for the Cheniere cultivar. Increased fissured-kernel percentages in response to HMCs below optimal levels agree with the findings of Siebenmorgen et al (1998Siebenmorgen et al ( , 2007.…”
Section: Resultssupporting
confidence: 83%
“…The PHRY was based on the assumption that all kernels that dry below 15% moisture and are rehydrated will fissure and result in broken kernels when milled. The 15% threshold moisture was based on laboratory tests (not reported) and is at the upper range of critical moistures reported by Siebenmorgen et al (1998). PHRY was calculated using equation 1:…”
Section: Methodsmentioning
confidence: 99%
“…A great deal of research beginning the 1930s showed that paddy rice kernels fissure when dried below a critical moisture content and then rehydrate because of exposure to free moisture or high humidity, (Kunze, 1993;Siebenmorgen et al, 1998;Lan et al, 1999). The fissured kernels break during milling, causing low HRY in lots with high amounts of fissured kernels.…”
Section: Abstract California's Medium-grain Rice Industry Experiencementioning
confidence: 99%
See 1 more Smart Citation